Electromagnetic wave propagation through a dielectric guide having piet hein cross-sectional geometry - Misra V.; Choudhury P.K.; Khastgir P.; Ojha S.P. (My University, 2025)
This article deals with a new type of dielectric guide, which has as its cross-sectional outline a Piet Hein curve. With the use of the scalar field approximation, eigenvalue equations for cutoffs have been derived for modes with different indices. Numerical results exhibit that the cutoff V value for the dielectric guide with Piet Hein cross-sectional geometry is intermediate between those of similar guides with square and circular cross sections; therefore, such a guide incorporates the properties of both square and circular waveguides. A study of these guides is advantageous because of the absence of corners, which reduces the scattering losses in rectangular dielectric waveguides. © 1996 John Wiley & Sons, Inc.